Diabetic foot ulcer in Malaysia: consensus on treatment patterns, health care utilization and cost - Nair, Harikrishna K.R.; Norlizah, P.; Mariam, M. N.; Alsagoff, Syed A.L.; Ming Long, Kam; Anantha, K. R.; Liew, Ngoh Chin; Ali Husien, Nizam (SAGE Publications Inc., 2025)
Healthcare resource utilization for Diabetic foot ulcers (DFUs) in Malaysia needs to be clarified. This modified Delphi panel study aimed to describe the clinical pathways for diabetic foot ulcer in Malaysia and to define the healthcare resources used and their costs. A systematic review of the literature was carried out on the management of diabetic foot ulcer in Malaysia. A modified Delphi panel involving 7 local experts was organized to validate the statements, in order to arrive at a consensus on the resources used for the treatment of DFU patients in Malaysia and their costs. A Markov model was then used to estimate the financial burden of DFU patients in Malaysia.The total cost per patient per annum was MYR 5981 in public and MYR 8581 in private setting. In the public setting, outpatient visits costs represent 50% of the overall cost, followed by medical devices which represent 38% of total costs. In the private setting, as in the public, outpatient visits and devices contribute the most to overall costs with 51% and 21%, respectively. However, hospital inpatient costs are higher in private setting and represent 14% of the total costs versus 5% in public setting.These findings may prove useful for clinicians and decision makers in understanding the economic implications of managing DFUs in Malaysia and the need for innovative therapies to reduce the burden for patients but also for the society.